2016
DOI: 10.3389/fpsyg.2015.01900
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Profiles of Classical, Jazz, and Rock Musicians: Genre-Specific Sensitivity to Musical Sound Features

Abstract: When compared with individuals without explicit training in music, adult musicians have facilitated neural functions in several modalities. They also display structural changes in various brain areas, these changes corresponding to the intensity and duration of their musical training. Previous studies have focused on investigating musicians with training in Western classical music. However, musicians involved in different musical genres may display highly differentiated auditory profiles according to the deman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 37 publications
5
38
0
3
Order By: Relevance
“…215-218) found metal musicians perceiving musical structures differently from Western music theory, it appears that rock fans perceive distorted tones differently from people who do not like this genre (Virtala & Tervaniemi, 2017, p. 398). This result accords with studies that demonstrated that characteristic musical features of certain genres are processed differently by musicians specializing in other genres (Tervaniemi, Janhunen, Kruck, Putkinen & Huotilainen, 2015;Vuust, Brattico, Seppänen, Näätänen & Tervaniemi, 2012). However, the triangulation results showed that while rock fans were less affected by the increased sensory unpleasantness of distortion than participants who do not like this genre, they still differed considerably from electric guitar players.…”
Section: Individual Differencessupporting
confidence: 89%
“…215-218) found metal musicians perceiving musical structures differently from Western music theory, it appears that rock fans perceive distorted tones differently from people who do not like this genre (Virtala & Tervaniemi, 2017, p. 398). This result accords with studies that demonstrated that characteristic musical features of certain genres are processed differently by musicians specializing in other genres (Tervaniemi, Janhunen, Kruck, Putkinen & Huotilainen, 2015;Vuust, Brattico, Seppänen, Näätänen & Tervaniemi, 2012). However, the triangulation results showed that while rock fans were less affected by the increased sensory unpleasantness of distortion than participants who do not like this genre, they still differed considerably from electric guitar players.…”
Section: Individual Differencessupporting
confidence: 89%
“…EEG studies have shown differences in sensitivity and amplitudes in MMN responses between musicians belonging to different genres 53,56 . On a behavioural level, drummers have been shown to be better at certain rhythmical tasks, yet the extent of these differences between types of musicians are not yet fully understood [57][58][59] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, contour and interval changes in a melody elicit larger MMNm responses (magnetic counterparts of the MMN recorded with magnetoencephalogram, MEG) in musicians than nonmusicians (Fujioka, Trainor, Ross, Kakigi, & Pantev, 2004). For the P3a response, plasticity induced by music expertise has been demonstrated for violations of Western music harmony that elicited enhanced P3a responses in folk musicians compared to nonmusicians (Brattico, Tupala, Glerean, & Tervaniemi, 2013; see also Tervaniemi, Janhunen, Kruck, Putkinen, & Huotilainen, 2015). Similarly, changes in interval width between consecutive notes in a melody elicited earlier and larger P3a responses (and later P3b responses) in musicians than nonmusicians (Trainor, Desjardins, & Rockel, 1999).…”
Section: G Uitar Distortion Has Been Intentionallymentioning
confidence: 95%